2020
DOI: 10.1002/pro.3807
|View full text |Cite
|
Sign up to set email alerts
|

Misannotations of the genes encoding sugar N‐formyltransferases

Abstract: Tens of thousands of bacterial genome sequences are now known due to the development of rapid and inexpensive sequencing technologies. An important key in utilizing these vast amounts of data in a biologically meaningful way is to infer the function of the proteins encoded in the genomes via bioinformatics techniques. Whereas these approaches are absolutely critical to the annotation of gene function, there are still issues of misidentifications, which must be experimentally corrected. For example, many of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…N ‐formylated sugars were first observed in 1985 on the lipopolysaccharides of certain strains of Pseudomonas aeruginosa but until recently were thought not to be widespread 48 . It is now known, however, that pathogens such as F. tularensis , Mycobacterium tuberculosis , Brucella melitensis , Providencia alcalifaciens , Salmonella enterica O60, Pantoea ananatis , Shewanella spp., and Pseudomonas congelans all have genes encoding for N ‐formyltransferases 15,17,19–23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…N ‐formylated sugars were first observed in 1985 on the lipopolysaccharides of certain strains of Pseudomonas aeruginosa but until recently were thought not to be widespread 48 . It is now known, however, that pathogens such as F. tularensis , Mycobacterium tuberculosis , Brucella melitensis , Providencia alcalifaciens , Salmonella enterica O60, Pantoea ananatis , Shewanella spp., and Pseudomonas congelans all have genes encoding for N ‐formyltransferases 15,17,19–23 …”
Section: Discussionmentioning
confidence: 99%
“…Given our interest in the biosynthesis of bacterial N ‐formylated sugars in pathogenic Gram‐negative bacteria such as C. jejuni , we were curious as to whether H. canadensis produces such sugars 14–24 . Analysis of the H. canadensis MIT 98‐5491 genome sequence suggested that HCAN_0197 , HCAN_0198 , HCAN_0204 , and HCAN_0200 encode for 4,6‐dehydratase, a 3,4‐ketoisomerase, a pyridoxal 5′‐phosphate or PLP‐dependent aminotransferase, and an N ‐formyltransferase, respectively.…”
Section: Introductionmentioning
confidence: 99%